Limites e possibilidades do enfermeiro na atenção pré-natal - Bortoli, Cleunir de Fatima Candido de (2015)
The gestational period is a singular moment in a woman's life, and conceives significant changes, involving biological, psychological, social and cultural aspects. The prenatal care understands the set of actions developed in the pregnancy monitoring, aiming at the development of pregnancy, childbirth and the birth of healthy forms. Several initiatives have been implemented by the Ministry of Health, focused on care for women during pregnancy, seeking to ensure the reduction of health problems related to maternal and child health. In this context of performing, the nurse is inserted as a member of the basic care team. This research has as guiding question for the study: How are developed care practices in the prenatal care by Nurses of Basic Care from a city of the Paraná State, Brazil? And as a general objective, to know the limits and possibilities of a nurse care practice of basic attention to prenatal health. And as specific objectives: to learn about the contributions of the nursing consultation on prenatal care, within the framework of the basic attention; know the factors that enable the performance of nurses within the framework of primary health care, in prenatal care; and knowing the limitations faced by nurses in prenatal care, within the framework of primary health care. In the method selection, it was decided by a field study, descriptive, qualitative approach. The study setting was composed by six basic health units, from a southwestern city of the Paraná State, Brazil. The participants of this research were seven nurses, involved in prenatal care, in the basic attention. For data collection, it was used a participant observation techniques and a semi structure interview from March up to August 2015. The data analysis and interpretation was guided by the Minayo operative proposal. The study was guided on the ethical aspects, according to Resolution number 466/12 of the National Health Council. This research had approved by the Research Ethics Committee of UFSM, according to the legal opinion number 909 903, under number of CAAE: 39437014.4.0000.5346. The results of this study includes three articles. In the first article, identified contributions of nursing consultation for prenatal care, with the inclusion of professional, reflecting on the possibility of pregnant women access to prenatal care and how important the space is for health education. In the second article, were unveiled the factors which propelled the nurse performing in the pregnant women care, which underlie the use of the protocols in the prenatal care and shelter as bond strategy, reflecting on accession of pregnant women to prenatal monitoring. In the third article, it was found the work of the nurses still faces challenges, portraying limitations on this practice, such as inadequate physical structure, the excessive demand of tasks and gaps assists in the service for attention to the maternal and child health. It is expected that the results of this study contribute to the qualification of prenatal care in the context of basic health care and to the consolidation of the nursing professional in the prenatal care.